2010
DOI: 10.1136/vr.b4881
|View full text |Cite
|
Sign up to set email alerts
|

Molecular typing of Mycobacterium bovis isolated from tuberculosis lesions of cattle in north eastern Ethiopia

Abstract: Mycobacterium bovis strains isolated from tuberculosis (TB) lesions from 1138 cattle slaughtered at Kombolcha abattoir in north eastern Ethiopia were characterised. Detailed postmortem examination, bacteriological culturing, regions of difference PCR and spoligotyping were used. At least one TB lesion was observed in 57 (5 per cent) of the cattle, of which 27 (47 per cent) yielded mycobacteria isolates. Of the 27 isolates, 25 were identified as M bovis and two as Mycobacterium tuberculosis. The M bovis isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
28
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 29 publications
7
28
3
Order By: Relevance
“…The distribution, frequency, and severity of lesions recorded in different tissues of camels were similar with the reports of similar studies in grazing cattle in Ethiopia [18], [32]. In these studies, the frequency and severity of the lesions were higher in the mesenteric lymph nodes than the thoracic lymph nodes, while in other studies under intensive cattle husbandry lesions were predominant in the respiratory tract and thoracic lymph nodes [14], [16].…”
Section: Discussionsupporting
confidence: 86%
“…The distribution, frequency, and severity of lesions recorded in different tissues of camels were similar with the reports of similar studies in grazing cattle in Ethiopia [18], [32]. In these studies, the frequency and severity of the lesions were higher in the mesenteric lymph nodes than the thoracic lymph nodes, while in other studies under intensive cattle husbandry lesions were predominant in the respiratory tract and thoracic lymph nodes [14], [16].…”
Section: Discussionsupporting
confidence: 86%
“…The overall prevalence of bTB from gross suspected TB lesion(s) in the present study was 2.78% which is comparable to 2.7% reported by Bekele and Belay [10], but lower than other findings ranging from 3.5% to 10.2% [79, 11–15, 25]. These variations could be explained by many factors including differences in the disease status in the animal populations, the sample size and the type of production system from where the slaughtered cattle were originated.…”
Section: Discussionsupporting
confidence: 78%
“…Other Ethiopian studies [715] undertaken at abattoirs have reported bTB in cattle based on TB-like lesion with an estimated average prevalence of 5.57%. In addition, M. bovis was also recovered from TB lesions in cattle, spoligotyped, and their strain types were identified and reported by previous studies in Ethiopia [7, 9, 1619]. Infection with M. bovis can be transmitted from cattle to humans, mainly through the consumption of contaminated milk and meat [20], although there is no evidence that this has happened in Ethiopia, where raw milk and meat consumption is widely habituated.…”
Section: Introductionmentioning
confidence: 96%
“…Such methods are also expensive, time consuming, laborious and not practical for surveillance purposes (Strong and Kubica 1985;Grange et al 1996;Parsons et al 2002;Warren et al 2006). Further, the interpretation of results is highly subjective and prone to errors such as those possible when interpreting differences in colony morphology (Strong and Kubica 1985;Grange et al 1996;Ameni et al 2010). Though also prone to inspector subjectivities and errors, meat inspection provides very significant insight into the prevalence of many infectious diseases and plays vital roles in both the quality assurance and quality control systems for the gross inspection of carcasses (Edwards et al 1997;Hinton and Green 1997;Asseged et al 2004).…”
mentioning
confidence: 99%